Inter-rater reliability of manual and automated region-of-interest delineation for PiB PET - Rosario, Bedda L.; Weissfeld, Lisa A.; Laymon, Charles M.; Mathis, Chester A.; Klunk, William E.; Berginc, Michael D.; James, Jeffrey A.; Hoge, Jessica A.; Price, Julie C. (NeuroImage (Orlando, Fla.), 2011)
A major challenge in positron emission tomography (PET) amyloid imaging studies of Alzheimer's disease (AD) is the reliable detection of early amyloid deposition in human brain. Manual region-of-interest (ROI) delineation on structural magnetic resonance (MR) images is generally the reference standard for the extraction of count-rate data from PET images, as compared to automated MR-template(s) methods that utilize spatial normalization and a single set of ROIs. The goal of this work was to assess the inter-rater reliability of manual ROI delineation for PiB PET amyloid retention measures and the impact of CSF dilution correction (CSF) on this reliability for data acquired in elderly control (n=5) and AD (n=5) subjects. The intraclass correlation coefficient (ICC) was used to measure reliability. As a secondary goal, ICC scores were also computed for PiB outcome measures obtained by an automated MR-template ROI method and one manual rater; to assess the level of reliability that could be achieved using different processing methods. Fourteen ROIs were evaluated that included anterior cingulate (ACG), precuneus (PRC) and cerebellum (CER). The PiB outcome measures were the volume of distribution (VT), summed tissue uptake (SUV), and corresponding ratios that were computed using CER as reference (DVR and SUVR). Substantial reliability (ICC≥0.932) was obtained across 3 manual raters for VT and SUV measures when CSF correction was applied across all outcomes and regions and was similar in the absence of CSF correction. The secondary analysis revealed substantial reliability in primary cortical areas between the automated and manual SUV [ICC≥0.979 (ACG/PRC)] and SUVR [ICC≥0.977/0.952 (ACG/PRC)] outcomes. The current study indicates the following rank order among the various reliability results in primary cortical areas and cerebellum (high to low): 1) VT or SUV manual delineation, with or without CSF correction; 2) DVR or SUVR manual delineation, with or without CSF correction; 3) SUV automated delineation, with CSF correction; and 4) SUVR automated delineation, with or without CSF correction. The high inter-rater reliability of PiB outcome measures in primary cortical areas (ACG/PRC) is important as reliable methodology is needed for the detection of low levels of amyloid deposition on a cross-sectional basis and small changes in amyloid deposition on a longitudinal basis. ►Manual ROI delineation provided high inter-rater reliability for PiB PET (ICC>0.8). ►CSF correction did not impact reliability of manual PiB PET measures. ►Highest inter-rater reliability was found in primary cortical areas. ►An automated ROI method agreed well with manual results in primary cortical areas.